2018
DOI: 10.1016/j.envpol.2018.04.069
|View full text |Cite
|
Sign up to set email alerts
|

Acute sensitivity of three Cladoceran species to different types of microplastics in combination with thermal stress

Abstract: Microplastics (<5 mm, MP) are ubiquitously distributed in the environment, causing increasing concern regarding their potential toxicity to organisms. To date, most research has focussed on the impacts of MPs on marine and estuarine organisms, with fewer studies focussing on the effects of microplastics on freshwater ecosystems, especially under different environmental conditions. In the present study, the sensitivity of two temperate Cladoceran species, Daphnia magna and Daphnia pulex, and a smaller tropical … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
54
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 94 publications
(58 citation statements)
references
References 56 publications
3
54
1
Order By: Relevance
“…This variation in species sensitivity may be inversely correlated with their body size (D. magna: D. pulex: C. dubia e 4.5:3:1 approximately) and therefore body volume. This is in line with previous studies comparing chemical toxicity of species with different body sizes, reporting the inverse correlation of sensitivity with body volume to copper nanoparticles, zinc, and microplastics (Song et al, 2015;Vesela and Vijverberg, 2007;Jaikumar et al, 2018). The metabolic rates of smaller sized species are higher than that of larger species (Vesela and Vijverberg, 2007).…”
Section: Discussionsupporting
confidence: 92%
See 4 more Smart Citations
“…This variation in species sensitivity may be inversely correlated with their body size (D. magna: D. pulex: C. dubia e 4.5:3:1 approximately) and therefore body volume. This is in line with previous studies comparing chemical toxicity of species with different body sizes, reporting the inverse correlation of sensitivity with body volume to copper nanoparticles, zinc, and microplastics (Song et al, 2015;Vesela and Vijverberg, 2007;Jaikumar et al, 2018). The metabolic rates of smaller sized species are higher than that of larger species (Vesela and Vijverberg, 2007).…”
Section: Discussionsupporting
confidence: 92%
“…We previously assessed the acute toxicity of PMP and SMP on the same three species (Jaikumar et al, 2018) and reported that at 18 C, species under study showed a similar acute sensitivity distribution as demonstrated in the present study (C. dubia > D. magna ! D. pulex).…”
Section: Discussionsupporting
confidence: 75%
See 3 more Smart Citations